2015
DOI: 10.1111/spc3.12162
|View full text |Cite
|
Sign up to set email alerts
|

Being Someone: The Integrated Self as a Neuropsychological System

Abstract: Fully functioning persons are characterized by a unity in thought, emotion, and action that amounts to “being someone” or having “an integrated self.” Psychologists have typically treated the integrated self as merely a descriptive term that summarizes significant behavioral achievements. In the present article, the authors seek to place the integrated self on firmer theoretical grounds by relating the integrated self to a neurobiological system with distinct processing characteristics. Building on personality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 101 publications
5
123
0
4
Order By: Relevance
“…The conceptual self is generally thought to be made up of one's attitudes and beliefs about one's values, preferences, past experiences and social roles (Kuhl, Quirin, & Koole, 2015). In contrast to the bodily self, the conceptual self is thought to emerge gradually during development via the association and organisation of intra-and interpersonal information closely related to one's behaviour and goals into a coherent network of self-relevant associations (Markus & Wurf, 1987;Perugini & Leone, 2009).…”
Section: Conceptual Selfmentioning
confidence: 99%
“…The conceptual self is generally thought to be made up of one's attitudes and beliefs about one's values, preferences, past experiences and social roles (Kuhl, Quirin, & Koole, 2015). In contrast to the bodily self, the conceptual self is thought to emerge gradually during development via the association and organisation of intra-and interpersonal information closely related to one's behaviour and goals into a coherent network of self-relevant associations (Markus & Wurf, 1987;Perugini & Leone, 2009).…”
Section: Conceptual Selfmentioning
confidence: 99%
“…Results revealed that subjects in the rational-reasoning condition were less satisfied with their choice when asked about 3 weeks after the experimental session compared to subjects who chose a poster intuitively. Reduced levels of satisfaction in the analytical group may have occurred because analytic processing typically abstracts from the emotional and personal meaning of a decision at hand (Kuhl et al, 2015). In other words, analytic processes reduce the complexity of a problem by breaking ambiguous information down to one aspect that is important in a particular situation (Dijksterhuis, 2004; Kuhl et al, 2015).…”
Section: The Advantages Of Intuitionmentioning
confidence: 99%
“…Reduced levels of satisfaction in the analytical group may have occurred because analytic processing typically abstracts from the emotional and personal meaning of a decision at hand (Kuhl et al, 2015). In other words, analytic processes reduce the complexity of a problem by breaking ambiguous information down to one aspect that is important in a particular situation (Dijksterhuis, 2004; Kuhl et al, 2015). This is of advantage for logical problem solving but of disadvantage when the problem includes divergent aspects that need to be considered (e.g., solving a complex personal problem; interpersonal relationships; dealing with an illness; see Kuhl et al, 2015).…”
Section: The Advantages Of Intuitionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] However, before and more than that it emphasizes internal controlling and purposeful auditing of individual's own actions and behaviors that is known as a "spiritual accounting", [5] or in the explanation of some writers, it has been called "self-controlling", [6] or "effective controlling system". [7,8] In Islamic principle, it is emphasized that man must be careful what he does, this means that if he decides to do a good work, he implements this decision soon and if he decides to do a bad work, he gives up this decision soon. [9,10] Quran by explaining, "whether you reveal what is in your hearts or hide it Allah will bring you to account for it", emphasizes on "know that Allah knows what is in your minds, therefore beware of him".…”
Section: Introductionmentioning
confidence: 99%